(untitled) - Pearson, Judy C. (Boston, Mass., 2003)
Human Communication: The Essentials is a completely refurbished version of the best-selling Human Communication: Understanding and Sharing by Judy Pearson and Paul Nelson. With The Essentials, Pearson and Nelson joined up with new co-authors Scott Titsworth and Lynn Harter to write an introduction to communication that ardently represents the contemporary field of communication studies. The authors approached the project with the mantra "Make It Smart; Keep It Real" so as to strike a practical balance of definitive content and everyday application. To make it smart the authors read hundreds of articles from such mainstream communication journals as Communication Education, Communication Monographs and Communication Studies. To keep it real the authors synthesized their findings so that they resonate with the challenges and goals of today's typical basic course. Every chapter features lively, respectful writing, critical thinking, innovative pedagogy and 21st century examples.
Keywords: Communication,Viễn thông